Adolescents' Health Awareness and Understanding of Cancer and Tumor Prevention: When and Why an Adolescent Decides to Consult a Physician. Issue 8 (22nd April 2016) - Magni, Chiara; Segrè, Chiara; Finzi, Cosimo; Veneroni, Laura; Clerici, Carlo Alfredo; Massimino, Maura; Casanova, Michela; Martinella, Vera; Chiaravalli, Stefano; Ricci, Angelo; Biondi, Andrea; Ferrari, Andrea
Abstract : Background: A feature often seen in adolescent patients with cancer is a lengthy symptom interval, especially in comparison with children. It has been suggested that inadequate awareness of cancer risk among adolescents may play an important role in this study. Methods: The Società Italiana Adolescenti con Malattie Onco‐ematologiche and the Fondazione Umberto Veronesi conducted a survey to investigate health awareness among healthy adolescents and their understanding of cancer and its signs and symptoms by commissioning a specialized agency (AstraRicerche). A questionnaire was administered to 500 Italian adolescents from the age group of 15 to 19 years using the computer‐aided web interviewing method. Results: Approximately 80% of the adolescents interviewed claimed to be well informed about their own health, 85% said they were aware that some lifestyle habits could influence their health, and 80% reported that they know that cancer can develop in adolescence too. It was also noted that, while some adolescents were worried about a given symptom, 22% of them reportedly preferred a wait‐and‐see approach (either to avoid alarming their parents, or they hoped that the symptom would be temporary). Conclusions: This study showed that a majority of adolescents are concerned about their own health, but sometimes prefer not to report their symptoms to anyone. Hence, it is important to develop information campaigns tailored to raise awareness among this age group and help them interpret their symptoms.